An anti-oxidative and conductive composite scaffold for cardiac tissue engineering. (15th October 2020) - Li, Junjie; Fang, Wancai; Hao, Tong; Dong, Dianyu; Yang, Boguang; Yao, Fanglian; Wang, Changyong
Abstract: Promising three-dimensional porous scaffolds for cardiac tissue engineering should both function as conductive substrates to adapt to the electroactive nature of the myocardium and modulate the excessive reactive oxygen species (ROS) microenvironment after myocardial infarction. In this study, glutathione (GSH) is grafted to the terminal carboxyl groups of carboxyl-capped aniline pentamer (CCAP), forming AP-GSH that is then introduced into gelatin (Gel) scaffold to create a composite scaffold combining both conductivity and antioxidant activity. Results suggest that the Gel/AP-GSH composite scaffolds exhibit high porosity, homogeneous pore structure and high swelling behaviors. The conductivity of the Gel/AP-GSH scaffold ranges from 3.4 × 10 −5  S/cm to 1 × 10 −4  S/cm, which is similar to the native myocardium. The introduction of AP-GSH can remove intracellular ROS and decrease the oxidative stress damage in brown adipose-derived stem cells (BADSCs), further improving the adhesion and proliferation of BADSCs under the ROS microenvironment. Moreover, BADSCs seeded in the Gel/AP-GSH composite scaffold maintain high cardiomyogenic differentiation even under the ROS microenvironment. These results demonstrate that Gel/AP-GSH composite scaffolds can be used as a promising candidate for cardiac tissue engineering. Graphical abstract: Image 1 Highlights: An anti-oxidative and conductive composite scaffold were prepared. The composite scaffold showed excellent mechanical strength, conductive activity and antioxidant properties. The scaffold can decrease the oxidative stress damage in cells. The scaffold can support the adhesion and cardiomyogenic differentiation of BADSCs.